2019
DOI: 10.1177/0021998319889110
|View full text |Cite
|
Sign up to set email alerts
|

Plastic deformation and fracture behaviors in particle-reinforced aluminum composites: A numerical approach using an enhanced finite element model

Abstract: A microstructure-based comprehensive finite element model, which incorporated the deformation/fracture of the matrix alloy, fracture of the particle and decohesion of interface, was built to predict the effects of particle size and shape on the plastic deformation and fracture behaviors in particle-reinforced metal matrix composites. The effect of particle size on the yield strength and work hardening rate of the matrix alloy was demonstrated. When the particle diameter is <10 µm, the fracture of the matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…So, more loads may be transferred from matrix to reinforcement at the sharp corner of hexahedron particles, which is consistent to homogeneous composites. 32,33 The stress state of SiCp is related to the layer orientation (θ). The statistics of orientation distribution without (Supplementary Figure S7(a)) and with (Supplementary Figure S7(b)) area weight were made.…”
Section: Load-bearing State Of Sic Particles and Al Matricesmentioning
confidence: 99%
See 3 more Smart Citations
“…So, more loads may be transferred from matrix to reinforcement at the sharp corner of hexahedron particles, which is consistent to homogeneous composites. 32,33 The stress state of SiCp is related to the layer orientation (θ). The statistics of orientation distribution without (Supplementary Figure S7(a)) and with (Supplementary Figure S7(b)) area weight were made.…”
Section: Load-bearing State Of Sic Particles and Al Matricesmentioning
confidence: 99%
“…The failure behavior of SiCp/Al network composite is clearly particle shape dependent, as illustrated in Figure 4. It can be observed that the crack length is larger for hexahedron particle (top surface of Figure 4(a)) because particles with sharp corner carry more loads 32,33 and thus more prone to fracture (Figure 2(a), curve declines early) than twenty-six face polyhedron and sphere particles. In addition, cracks also exist in PaW (marked by circles, Figure 4), but the ductile Al matrix may prevent the crack propagation in PaW.…”
Section: Fracture Behavior Of the Network Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…It was concluded that the interface strength and the particle arrangement have considerable influences on the strength and failure strain of PRMMCs. An RVE model was proposed to investigate fracture behaviors in Al6061/SiC composites using CZM for interface decohesion and Griffith criterion for the particle fracture [ 18 ]. A high interfacial Al/SiC bonding was noticed and the interfacial debonding occurred during the crack growth from the particle to the interface.…”
Section: Introductionmentioning
confidence: 99%